2008
DOI: 10.1097/shk.0b013e31815d19ad
|View full text |Cite
|
Sign up to set email alerts
|

LPS-Induced Vascular Endothelial Growth Factor Expression in Rat Lung Pericytes

Abstract: Vascular endothelial growth factor (VEGF) is a potent angiogenic and vascular permeability factor. Recent studies have shown that the VEGF levels increase in several cell types, for example, macrophages and smooth muscle cells after LPS stimulation, suggesting that it is important in the initiation and development of sepsis. In particular, LPS-regulated contractility in lung pericytes may play an important role in mediating pulmonary microvascular fluid hemodynamics during sepsis. This study investigated the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
2
10
0
1
Order By: Relevance
“…Our results clearly showed that production of NO was blocked by pre-incubation of pericytes with these drugs. These results agree with those obtained from lung microvascular pericytes [29] and indicate that similar mechanisms are involved in activation of brain microvascular pericytes by LPS.…”
Section: Discussionsupporting
confidence: 92%
“…Our results clearly showed that production of NO was blocked by pre-incubation of pericytes with these drugs. These results agree with those obtained from lung microvascular pericytes [29] and indicate that similar mechanisms are involved in activation of brain microvascular pericytes by LPS.…”
Section: Discussionsupporting
confidence: 92%
“…46,47 Increased vascular permeability, induced by VEGF, is reported in different microvasculatures, including the lung. 48,49 Our data are consistent with those of Picciotti and colleagues 50 and Selivanova and colleagues, 51 who found that noise stimulation significantly increases VEGF expression in the stria vascularis. 50 …”
Section: Noise Damages the Blood-labyrinth Barrier And Induces Vasculsupporting
confidence: 82%
“…In certain types of cells, LPS induces angiogenic factors, such as vascular endothelial growth factor (VEGF). 10,11 Because cholangiocytes express the receptor of LPS, Toll-like receptor 4 (TLR4), 12,13 LPS may also be able to induce angiogenic growth factors in cholangiocytes.…”
mentioning
confidence: 99%